Annaes maritimos e coloniaes: publicacão mensal redigida sob a direcção da Associação maritima e colonial (Imprensa nacional, 1844)
Keywords: 10.Cover Damage; 2.Damage; Associação maritima e colonial (Lisbon); Colonisation Périodiques; Colonization; Colonization Periodicals; Condition: Fair; Hard Cover; History; Magazine; Periodicals; Portugal Colonies Periodicals; Portugal Colonies Périodiques; Portuguese colonies; Périodiques; periodicals

Meditacoes ou Discursos Religiosos - Bastos, Jose Joaquim Rodrigues (Na Imprensa Nacional, 1844)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Encyclopedie Catholique - Glaire, M. L'abbe (1844)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Encyclopédie Catholique: répertoire universel et raisonné des sciences, des lettres, des arts et des métiers, formant une bibliothèque universelle - Jean Baptiste Glaire (Parent-Desbarres, 1844)
Keywords: Encyclopédie Catholique; Hard Cover; Religion

Tractados de Theologia Moral - Magalhaens, Joaquim Jose de (1844)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Tractados de Theologia Moral - Magalhaens, Joaquim Jose de (1844)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Diccionario da lingua portugueza. T. 1 A - E - Silva, António de Morais (Antonio José da Rocha, 1844)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Dictionaries; Hard Cover

Diccionario da lingua portugueza. T. 2 F - Z - Silva, António de Morais (Antonio José da Rocha, 1844)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Dictionaries; Hard Cover